Mechanism for Activation of Triosephosphate Isomerase by Phosphite Dianion: The Role of a Ligand-Driven Conformational Change - Malabanan, M. Merced (2011)
The L232A mutation at triosephosphate isomerase (TIM) from Trypanosoma brucei brucei results in a small 6-fold decrease in k(cat)/K(m) for the reversible enzyme-catalyzed isomerization of glyceraldehyde 3-phosphate to give dihydroxyacetone phosphate. By contrast, this mutation leads to a 17-fold increase in the second-order rate constant for the TIM-catalyzed proton transfer reaction of the truncated substrate piece [1-(13)C]-glycolaldehyde ([1-(13)C]-GA) in D(2)O; a 25-fold increase in the third-order rate constant for reaction of the substrate pieces GA + and phosphite dianion (HPO(3)(2-)); and a 16-fold decrease in K(d) for binding of HPO(3)(2-) to the free enzyme. Most significantly, the mutation also results in an 11-fold decrease in the extent of activation of the enzyme towards turnover of GA by bound HPO(3)(2-). The data provide striking evidence that the L232A mutation leads to a ca. 1.7 kcal/mol stabilization of a catalytically active loop-closed form of TIM (E(c)) relative to an inactive open form (E(o)). We propose that this is due to the relief, at L232A mutant TIM, of unfavorable steric interactions between the bulky hydrophobic side chain of Leu-232 and the basic carboxylate side chain of Glu-167, the catalytic base, which destabilize E(c) relative to E(o).